Does the Order of Information Affect Investors' Investment Decisions? Experimental Investigation - Riyadi Aprayuda; Fauzan Misra; Rayna Kartika (Journal of Accounting and Investment, 2021)
Research aims: This study examines the order of information’s effect according to the Belief Adjustment Model. In particular, this study investigates the effect of the direction of the order and the pattern of presenting information in making investment decisions.Design/Methodology/Approach: The research applied an experimental method with web-based instruments using a 2x2 factorial design between subjects, involving 65 investors.Research findings: The investors’ investment valuation who received negative to positive information sequence direction was higher than the investors who received positive to negative information direction. Furthermore, there was an order effect in the form of recency on investors who received a partial presentation pattern. Meanwhile, investors who received a simultaneous pattern did not show an order effect in their assessment. These findings underline that the simultaneous pattern could reduce the order effect, so that investors need to generalize the information as a whole to avoid this bias.Theoretical contribution/Originality: This study extends the investigation of investment decisions using a long sequence of information perspectives and more varied types of information (e.g., financial information, corporate governance, and industry sectoral information that has an impact on company conditions) in making investment decisions on the belief adjustment model.Practitioner/Policy implication: Companies must maintain the direction of the order and the presentation patterns when issuing company information to maintain the quality of investors' decisions and avoid the risk of volatility in company shares.Research limitation/Implication: Participants who joined this research were active investors but had not yet had a comprehensive experience.